Analysis of Factors Associated with Knowledge, Attitudes, and Practices Regarding Refractive Amblyopia Among Parents of Children with Refractive Amblyopia - Thanh Van, Nguyen; Hong Giang, Do; Minh Chi, Vuong; Van Nghia, Bui (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 4, 2025)
Abstract : Objective: To analyze several factors associated with the knowledge, attitudes, and practices (KAP) of parents of children with amblyopia caused by refractive errors. Methods: A cross-sectional descriptive study was conducted on 280 parents of children diagnosed with amblyopia induced by refractive errors. Results: Better knowledge of refractive errors was observed among parents under 40 years old, living in urban areas, with education levels above high school, having a family history of refractive amblyopia, and obtaining information about amblyopia from the Internet (p<0.05). More favorable attitudes were found in parents with higher education levels, those bringing their children for follow-up eye examinations (from the second visit onwards), and those with a family history of refractive errors (p<0.05). Better practices in preventing refractive amblyopia were associated with urban residence, higher education, a family history of refractive amblyopia, and acquiring information from the Internet (p<0.05). A positive correlation was found among knowledge, attitudes, and practices of parents (r>0). Parents with good knowledge were 2.307 times more likely to have positive attitudes and 2.044 times more likely to adopt appropriate practices compared to those with inadequate knowledge. Conclusion: The knowledge, attitudes, and practices regarding refractive amblyopia among parents are significantly associated with age, educational level, and family history of the condition. Attitudes and practices are better among parents with a family history of refractive amblyopia, while practices are also influenced by urban residence. Parents with better knowledge are more likely to exhibit better attitudes and practices. Keywords: Refractive error, knowledge, attitude, practice, parents.